1H NMR and MS based metabolomics study of the therapeutic effect of Cortex Fraxini on hyperuricemic rats. (5th June 2016) - Wang, Yinan; Zhao, Min; Xin, Yi; Liu, Jiajia; Wang, Miao; Zhao, Chunjie
Abstract: Ethnopharmacological relevance: Cortex Fraxini (CF) is an important traditional Chinese herbal medicine used for the treatment of gout and hyperuricemia. Aim of the study: The aim of this study was to evaluate the anti-hyperuricemic effect of CF on hyperuricemic rats and to investigate its mechanism of action. Materials and methods: Metabolomics based on NMR and MS was used to study the therapeutic effect of CF on hyperuricemic rats. Plasma determination of uric acid (UA) showed that CF treatment markedly improved the UA level. Subsequently, metabolomics analysis was conducted using samples of plasma, kidney and urine, and orthogonal partial least squares-discriminant analysis (OPLS-DA) combined with principal component analysis (PCA) were used to detect potential biomarkers. Results: A total of 26 biomarkers were identified as being primarily involved in amino acid metabolism, lipid metabolism, purine metabolism, amino acid metabolism and carbohydrate metabolism, and hyperuricemia can disturb the balance of many of these metabolic pathways in vivo . Conclusions: The variations in biomarkers revealed the therapeutic mechanism of CF, and a number of these biomarkers are not only significant for early diagnosis but also for predicting hyperuricemia. Graphical abstract: